Validation of reference genes for the normalization of RT-qPCR gene expression in Bacillus siamensis 1021 grown in different culture media - Warinya Nuwong; Chokchai Kittiwongwattana (Iranian Journal of Microbiology, 2022)
Background and Objectives: 1021. Materials and Methods: was used for assessment of the best candidate genes. Results: expression in potato dextrose broth and mineral salt medium, respectively. Conclusion: 1021 in these media. This study emphasized the significance of reference gene validation for gene expression analysis and provided a guideline for future gene expression studies in
Keywords: Molecular Biology Techniques and Applications; Genomics and Phylogenetic Studies; Animal Genetics and Reproduction